Effects of soaking and gelatinization process on the quality of semi-dry rice noodles - ZHOU Yong-sheng; LI You; ZHAO Hai-yan; LONG Yong-yi; JIANG Cai-yun; CAI Ji-xiang (Shipin yu jixie)
Objective: The main objective of this study was to optimize the soaking and gelatinization process of semi-dry rice noodles. Methods: Taking semi-dry rice noodles as the research object, the effects of soaking temperature, soaking time, gelatinization temperature, gelatinization time and water addition amount on the cooking loss rate and texture characteristics were analyzed, and the better soaking process and gelatinization process were obtained. Results: Soaking temperature 40 ℃, soaking time 2 h, gelatinization temperature 90 ℃, gelatinization time 8 min, water addition 70% were the best process conditions. The semi-dry rice noodles prepared under the optimal process has better cooking quality and texture characteristics. Conclusion: The quality of semi-dry rice noodles can be improved by optimizing the soaking process and gelatinization process.